Overhouse - Parfitt, Mark (Gallery Central North Metropolitan TAFE, 2020)
A solo exhibition of the home as a site for sculpture. Combining DIY construction, audience participation and the artist’s own house, the project contributes to conversations seeking new understandings of homemaking beyond the expectations of ordinary living in the suburbs of Perth.